Serious Games Accessibility Design Model for Low-Vision Children - Nurul Izzah Othman; Hazura Mohamed; Nor Azan Mat Zin (Advances in Human-Computer Interaction)
The evolution in information technology has brought worldwide access to information. Information technology has become an approach for effective learning in the education sector. This development provides an opportunity for people with disabilities. However, many educational software and applications in the market, such as serious games, cannot be accessed by low-vision children due to the visual properties in game design. For instance, small text and graphic sizes, lack of colour contrast, complex visual effects, or reliance on visual cues for instructions are among the visual properties that contribute to these accessibility challenges. They can play serious games as long as they are designed based on their accessibility needs. This paper proposed a serious games design model for low-vision children. The three main components are accessibility, game design, and pedagogy. The serious game accessibility design model is implemented using a low-fidelity prototype that takes the form of a serious game mockup. This prototype allows for basic interaction and testing of the game’s features, with a focus on accessibility considerations. The expert validation was conducted on the prototype using heuristic evaluation to assess its usability. Based on the evaluation, the experts agreed on implementing the proposed model to the prototype.